Experimental study on the effect of bed aspect ratio to the drying rate of chilli for swirling fluidized bed dryer - Mohamad Firdaus, Basrawi; F., Redzlan; Thamir K., Ibrahim; Ahmmad Shukrie, Md Yudin (IOP Publishing, 2020)
Swirling Fluidized Bed Dryer (FBD) has better performance because of the improvement of air flow with less pressure drop. However less study focus on the performance of swirling FBD especially at small-scale. Thus, the objective of this study is to investigate drying characteristics of green chillies at different ratio of chilli, Rchilli and bed aspect ratio, RBed by the swirling fluidized bed dryer. An electrical blower with 600 W of power was used as a main source to supply air at flow rate of 0.324 kg/s which equals to the velocity at the distributor of 8.25 m/s. The chamber has 400 mm height and 150 mm diameter with maximum capacity of 2 kg. The air distributor used has 67% inclination angle to provide air swirling inside the FBD. It was found that RBed increased from 0.8 to 1.6, the drying performance decreased in which the final moisture ratio was higher at 0.72-0.79 for RBed =1.6 as compared to better moisture ratio at 0.18-0.24 for RBed = 0.8. The drying rate was at 0.225-0.275 %/min for RBed = 0.8, and 0.075-0.10 %/min for RBed = 1.6. When the Rchilli increased from 1:1 to 2:1, the drying performance showed slightly decreased. Moisture ratio also slightly increased from 0.18 to 0.24 for RBed = 0.8, whereas from 0.72 to 0.79 for RBed = 1.6. This finding suggest that the RBed has more significant effect than Rchilli.